Influência da artrite encefalite caprina sobre a expressão de rnam para gdf-9, bmp- 15 e bmpr-ib em folículos ovarianos e ativação in vitro de folículos primordiais em meio suplementado com fitohemaglutinina e egf. - Lopes, Tânia de Azevedo (2014)
This study aims to investigate the effects of caprine arthritis encephalitis (CAE) on the expression of BMP-15, BMPR-IB and GDF-9 in ovarian follicles, as well as the effects of phytohemagglutinin (PHA) and EGF on the survival and activation of primordial follicles, and on expression of mRNA for TNF-α and its receptors in cultured goat ovarian tissue. The levels of BMP-15, BMPR-IB and GDF-9 in primordial/primary and secondary follicles, as well as in COCs and follicular walls from antral follicles were evacuated by real-time PCR (experiment 1). Ovarian tissues were cultured for six days in α-MEM+ alone or supplemented with EGF (100μg/mL), PHA (10μg/mL) or both (experiment 2). Before and after culture, ovarian fragments were processed for morphological analysis or stored to evaluate the expression of mRNA for TNFα and its receptors. The results showed that the expression of BMP-15 and GDF-9 in primordial/primary follicles from infected goats was significantly higher than in health animals, but the expression of GDF-9 in secondary follicles from infected goats was significantly lower. Additionally, the expression of mRNA for BMP-15 in follicular wall of antral follicles from infected goats was significantly higher than in healthy goats. After culturing ovarian fragments in all tested media, reduced percentages of primordial follicles, and increased of developing follicles was observed when compared to uncultured control. Furthermore, there was a significant increase in follicular diameter after culture in medium supplemented with EGF. Ovarian tissue from infected goats cultured in medium supplemented with PHA had primordial follicles with higher diameters than those from healthy animals. An increase in the levels of mRNAs for TNF-α was observed after culturing ovarian tissue in presence of both EGF and PHA in healthy animals, but this same treatment promoted a reduction of mRNAs for TNF-α and and increase of TNFR-II transcripts in infected animals. In conclusion, CAE influences the expression of mRNA for BMP-15 and GDF-9 in goat ovarian follicles and PHA and EGF differentially regulate the expression of TNFα and TNFR-II in cultured ovarian tissue.